3D Virtual Reality Imaging of Major Aortopulmonary Collateral Arteries: A Novel Diagnostic Modality. Issue 6 (November 2021) - van de Woestijne, Pieter C.; Bakhuis, Wouter; Sadeghi, Amir H.; Peek, Jette J.; Taverne, Yannick J.H.J.; Bogers, Ad J.J.C.
Background: Major aortopulmonary collateral arteries (MAPCAs), as seen in patients with pulmonary atresia, are arteries that supply blood from the aorta to the lungs and often require surgical intervention. To achieve complete repair in the least number of interventions, optimal imaging of the pulmonary arterial anatomy and MAPCAs is critical. 3D virtual reality (3D-VR) is a promising and upcoming new technology that could potentially ameliorate current imaging shortcomings. Methods: A retrospective, proof-of-concept study was performed of all operated patients with pulmonary atresia and MAPCAs at our center between 2010 and 2020 with a preoperative computed tomography (CT) scan. CT images were reviewed by two congenital cardiac surgeons in 3D-VR to determine additional value of VR for MAPCA imaging compared to conventional CT and for preoperative planning of MAPCA repair. Results: 3D-VR visualizations were reconstructed from CT scans of seven newborns where the enhanced topographic anatomy resulted in improved visualization of MAPCA. In addition, surgical planning was improved since new observations or different preoperative plans were apparent in 4 out of 7 cases. After the initial setup, VR software and hardware was reported to be easy and intuitive to use. Conclusions: This study showed technical feasibility of 3D-VR reconstruction of children with immersive visualization of topographic anatomy in an easy-to-use format leading to an improved surgical planning of MAPCA surgery. Future prospective studies are required to investigate the clinical benefits in larger populations.